Una aproximación a la relación entre objeto matemático y sentidos - Rojas G., Pedro J. (Revista Científica, 2011)
This article is a review of studies on the relationship between mathematical object and the senses assigned to those objects. This work is located in semiotic context and studies in general the relationship semiosis-noesis in the construction of mathematical knowledge. Studies which without be exhaustive, includes aspects of mathematical activity, the communication on emerging mathematical objects and the learning mathematical objects.